Practical approaches to the use of markers of biochemical hyperandrogenism in women - T.M. Tutchenko; O.A. Burka; I.V. Sidorova; I.H. Nohovska; I.M. Marynchyna; N.M. Shcherbatiei (Publishing House TRILIST, 2022)
Hyperandrogenism (HA) remains an actual problem that raises a large number of questions, in particular, in cases of discrepancy between the clinical signs of HA and biochemical parameters. This review includes an analysis of recent studies of androgen synthesis and metabolism in healthy women of reproductive age; management of pathologies accompanied by HA; as well as contemporary approaches to the principles of prescribing and evaluating the results of the main available markers of biochemical HA. There are сoncepts of clinical and biochemical HA. Biochemical HA is an increase in the levels of various circulating androgens. The concept of clinical HA includes hirsutism as assessed by the modified Ferriman-Gallwey scale. The most common causes of HA include polycystic ovary syndrome, non-classical forms of congenital adrenal hyperplasia, other endocrine disorders. It is necessary to carry out a differential diagnosis of these conditions with more rare causes as a primarily tumor pathology. The choice and evaluation of laboratory markers of biochemical HA should be made taking into account clinical data such as puberty history, anovulation, polycystic ovarian morphotype, obesity; presence and degree of hirsutism and/or other androgen-associated dermatopathies, the characteristics of the course of clinical HA (sudden onset, rapid progression), presence of other endocrinopathies, liver and kidney dysfunction; diabetes mellitus. The objectives of the laboratory assessment of HA are determination of HA severity; determination of the source of excess androgen synthesis (ovaries, adrenal glands); assessment of the free fraction of circulating active androgens; in some cases, assessment of the formation of active androgens in the skin. The following indicators are used to solve the tasks in laboratory diagnostics: total testosterone, free testosterone, free androgen index, androstenedione, dehydroepiandrosterone sulfate, 17-hydroxyprogesterone, dihydrotestosterone. A comprehensive assessment of these indicators allows not only assessing the presence of HA and its severity, but also the nature of its leading and secondary components, which determine the presence and prognosis of metabolic risks and allow individualizing therapeutic approaches.